A highly adhesive siloxane LED encapsulant optimized for high thermal stability and optical efficiency. Issue 46 (11th November 2016) - Kim, Yong Ho; Lim, Young-Woo; Lee, Daewon; Kim, Yun Hyeok; Bae, Byeong-Soo
Abstract : Herein, a highly adhesive LED encapsulant (HAEncap) is proposed based on a phenyl siloxane hybrid material with a high thermal stability, refractive index, and transparency which uses cost-effective radical polymerization. Abstract : Herein, a highly adhesive LED encapsulant (HAEncap) is proposed based on a phenyl siloxane hybrid material, with a high thermal stability, refractive index, and transparency, which uses cost-effective radical polymerization. The radical polymerization of the HAEncap noticeably increases the adhesion strength without the addition of any adhesion promoters exhibiting better transmittance, refractive index and thermal stability compared to other commercialized LED encapsulants using hydrosilylation.